Golf trainer safety practises in indoor simulators: impact on trust and exercise continuation - Junghoon Ha; Doojin Kim; Kwangwoo Nam (Frontiers in Psychology, 2025)
IntroductionThis study examines the relationship between safety management, trainer trust, training satisfaction, and exercise continuity in golf lessons, focusing on Korea's growing participation in sports amid rising safety concerns.MethodsData were collected via convenience sampling from 215 adults participating in golf lessons at an indoor driving range with a golf simulator in Seoul, Korea. After excluding 13 unreliable responses, 202 responses were analysed using IBM SPSS Statistics 21 and AMOS 21. Frequency analysis, confirmatory factor analysis, correlation analysis, and structural equation modelling were conducted.ResultsParticipants' perception of the trainer's safety management positively affected their trust in the trainer (t = 13.727, p < 0.001) and their training satisfaction (t = 14.402, p < 0.001). However, perceived safety management did not show a statistically significant direct effect on exercise continuation (t = −0.502, p > 0.05). Trust in the trainer was positively associated with participants' intention to continue exercise (t = 4.406, p < 0.001), whereas training satisfaction was not (t = 0.323, p > 0.05).DiscussionEmphasising safety and leadership skills among golf trainers is crucial for fostering a safe exercise environment. This can enhance trust and satisfaction among participants, thereby promoting their commitment to an exercise routine and positively impacting trainer retention. These findings highlight the need for improved safety training protocols for golf instructors in indoor facilities to enhance learner retention.